Map of sensitivity biota of the North Caspian to oil pollution (Experimental biology, 2016)
This paper proposes a quantitative method of mapping the sensitivity of biota to oil pollution of the environment and is an example of mapping for the Northern Caspian.
Keywords: biota; sensitivity of biota to pollution; quantitative mapping; environmental risks; biodiversity.